Pemanfaatan Lagu Anak-Anak Sebagai Media Pendidikan Taman Kanak Kanak - Rosiman Iskandar; Ahmad Rafik (Jurnal Pendidikan Tuntas, 2024)
Character education is the basis for realizing the vision of national development, namely to create a society with noble, moral, ethical, cultured and civilized character based on the Pancasila philosophy. Character education at an early age is very important, because by instilling strong character in children, it is hoped that they will become the next generation of the nation who are strong and have character in accordance with Indonesia's noble values ​​and can overcome current national problems. The purpose of this research is to show and provide an overview of the use of children's songs as a medium for character and character education in kindergarten Tuah Negeri Pekanbaru This research is qualitative research so it will produce descriptive data in the form of words. Observation techniques, document study and interviews were used in the data collection process. The technique for checking the validity of the data is by checking the degree of trust in the data, namely using data triangulation, with the crosscheck method of data and data sources. This research uses three stages in data analysis, namely data reduction, data presentation, and drawing conclusions. The research results show that children's songs can be used as a medium for character education in early childhood. The character education process occurs when the teacher teaches children's songs and explains the content or meaning contained in the song being taught. The characters contained in children's songs vary greatly, including: religious, honest, disciplined, hard working, independent, democratic, curious, national spirit, love of the country, friendly/communicative, love of peace, environmental care, social care, responsibility. To measure the success of character education in kindergarten Tuah Negeri Pekanbaru teachers observe changes in children's attitudes and behavior while they are at school. Keywords: Utilization, Media, Songs